METHODOLOGY FOR MANAGING SUSTAINABLE ENTERPRISE DEVELOPMENT: DEFINITION AND STRUCTURE - Оксана Ковтун (Економіка та суспільство)
The methodology of activity is a basic feature that determines the entire range of methodological support that can be used to solve a particular scientific or practical problem, i.e., it is the basis for the relevant research results. Therefore, determining the methodology for managing the sustainable development of an enterprise is an urgent scientific task. The article is aimed at clarifying the essence and components of the methodology for managing the sustainable development of enterprises. The article presents a literature review and conceptualizes the methodology for managing sustainable enterprise development as a systemic set of methods, approaches, tools, and scientific cognition techniques. This conceptualization ensures a comprehensive exploration of the socio-economic environment, the determination of truths, and the identification of transformation directions for achieving sustainable enterprise development under contemporary economic conditions. The efficiency of implementing modern methodological approaches to managing sustainable enterprise development has been demonstrated using the practices of leading global manufacturers. The implementation of the sustainability management methodology in the practical activities of enterprises makes it possible to accelerate the processes of adaptation to external transformations, proactively anticipate them, implement internal changes, review and adjust strategies based on feedback, and increase the level of sustainability and competitiveness.